PKM PELATIHAN PEMBUATAN HANDSANITIZER BERBAHAN DASAR ALAM BAGI IBU-IBU KOMPLEKS CITRA MAS - Sitti Faika; Bakhrani A. Rauf; Suwardi Annas (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Covid 19 is a pandemic disease that is not only take effected by Indonesian people, but this extraordinary incident is also hit by almost all countries in the world, with the number of positive Covid 19 rising gradually, the numbers counting more than 1000 people per day based on World Health Organization (WHO) data. Covid 19 is a disease caused by a virus that attacks the respiratory tract with an incubation time ranging from 5 to 14 days, to fighting this pandemic disease, the awareness of the public is the importance, one of which is the use of a hand sanitizer. The importance of health education in fighting the C0vid 19 virus among mothers is the goal of this PKM, started on the family education, due to the mother is the most importen person biside father in the household, for that the PKM targets are mothers in the complex for making Hand sanitizer. From the results of the training, it was concluded that the enthusiasm of the Citra Mas complex women was great in participating.   The training started by providing information about the importance of maintaining health during a pandemic among families, how to make hand sanitizers using natural ingredients such as aloe vera, and how to packing.